The potential of bamboo and the contribution of bamboo craftsmen to the community's income in Cibadak Village, Bogor City, Indonesia - Zainal Muttaqin; Abdul Rahman Rusli; Bambang Supriyanto (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Muttaqin Z, Rusli AR, Supriyanto B. 2023. The potential of bamboo and the contribution of bamboo craftsmen to the community's income in Cibadak Village, Bogor City, Indonesia. Biodiversitas 24: 5796-5807. Bamboo is a plant of rural communities that can be used for various purposes in people's lives. Cibadak Village is thought to have a substantial number of bamboo potentials, but the exact amount has yet to be discovered. Likewise, the contribution of income obtained from bamboo-cage craftsmen is also unknown, so studies on this issue are essential. This research aimed to determine the potential availability of plants and the contribution of bamboo craftsmen to the income of the people of Cibadak Village, Tanah Sareal Sub-district, Bogor City, West Java Province, Indonesia. The collection of data was conducted through field research and bibliographic research. This research concluded that the potential of bamboo in Cibadak Village was only 6.72 ha or 2.04% of the total area, and the contribution of bamboo craftsmen to the community's income was less significant (27.03%) compared to the average total income of the community. However, the income of bamboo craftsmen more than the other income contribution came from drivers (25.00%), merchants (21.67%), and construction workers (26,30%). Only 20% of respondents consider the revenue of bamboo craftsmen as the main job, and 80% of the revenue is side income to complete revenue from the other job. The species of bamboo were found of bambu tali (Gigantochloa apus), bambu betung (Dendrocalamus asper), bambu ampel hijau (Bambusa vulgaris var. vitata), bambu ampel kuning (Bambusa vulgaris var. striata), and bambu andong (Gigantochloa pseudoarundinacea).  Bambu tali are the most commonly found in Cibadak Village, consisting of 279 clumps (80.87%) and 25,028 culms (90.70%), while other bamboo species were found in small numbers. The bamboo craftsmen use all raw materials of Bambu tali (Gigantochloa apus), and a few people also utilize bamboo shoots of Bambu betung and Bambu ampel for self-consumption as complementary food vegetables.